PERAN MANAJEMEN SEKURITI DALAM DUNIA DIGITAL: PENDEKATAN DAN KENDALA DALAM PERLINDUNGAN DATA BISNIS - Abi Maulana Sugiartono; Achmad Yasril, Daffa Habibie Sumantry, Dimas Aditya Nugraha, Irfan Nur Arif, Putra Bagus Nugroho, Ra (ADISAM PUBLISHER, 2024)
This research aims to understand the important role of security management in protecting business data in the digital era. With increasingly complex challenges, security management is key to overcoming data protection barriers. Through evaluating various organizational approaches to security management, this research identifies the obstacles faced in maintaining business data security. This research also explores how digital technology can increase the effectiveness of security management, while considering the risks and challenges that arise. The research results are expected to provide new insights for practitioners and researchers about improving security management for better business data protection in the digital world.